Association of Apoptosis-Mediated CD4+ T Lymphopenia With Poor Outcome After Type A Aortic Dissection Surgery - Luo, Wei; Sun, Jing-Jing; Tang, Hao; Fu, Di; Hu, Zhan-Lan; Zhou, Hai-Yang; Luo, Wan-Jun; Xu, Jun-Mei; Li, Hui; Dai, Ru-Ping (Frontiers in Cardiovascular Medicine, 2021)
Background: Many patients with type A aortic dissection (AAD) show low lymphocyte counts pre-operatively. The present study investigated the prognostic values of lymphopenia and lymphocyte subsets for the postoperative major adverse events (MAEs) in AAD patients undergoing surgery, and explore mechanisms of lymphopenia. Methods: We retrospectively analyzed pre-operative lymphocyte counts in 295 AAD patients treated at two hospitals, and evaluated their correlation with MAEs. We prospectively recruited 40 AAD patients and 20 sex- and age-matched healthy donors (HDs), and evaluated lymphocyte subsets, apoptosis, and pyroptosis by flow cytometry. Results: Multivariable regression analysis of the retrospective cohort revealed pre-operative lymphopenia as a strong predictor of MAEs (odds ratio, 4.152; 95% CI, 2.434–7.081; p < 0.001). In the prospective cohort, lymphocyte depletion in the AAD group was mainly due to loss of CD4+ and CD8+ T cells as compared with HDs (CD4+ T cells: 346.7 ± 183.6 vs. 659.0 ± 214.6 cells/μl, p < 0.0001; CD8+ T cells: 219.5 ± 178.4 vs. 354.4 ± 121.8 cells/μl, p = 0.0036). The apoptosis rates of CD4+ and CD8+ T cells were significantly higher in AAD patients relative to HDs (both p < 0.0001). Furthermore, the pre-operative CD4+ T cells count at a cut-off value of 357.96 cells/μl was an effective and reliable predictor of MAEs (area under ROC curve = 0.817; 95% CI, 0.684-0.950; sensitivity, 74%; specificity, 81%; p < 0.005). Pre-operative lymphopenia, mainly due to CD4+ T cells exhaustion by apoptosis, correlates with poor prognosis in AAD patients undergoing surgery. Conclusion: Pre-operative lymphopenia in particular CD4+ T lymphopenia via apoptosis correlates with poor prognosis in AAD patients undergoing surgery.